2018
DOI: 10.1002/pen.24862
|View full text |Cite
|
Sign up to set email alerts
|

Durable pressure filtration membranes based on polyaniline–polyimide P84 blends

Abstract: A pressure filtration membrane from conducting polymer polyaniline (PANI) is known to possess low mechanical strength and thermal stability. Therefore, it is believed that the properties of the membrane can be enhanced by blending PANI with a conventional polymer like polyimide (PI), which possesses high mechanical strength and thermal stability. A thermal analysis revealed that polymer chain of blend membranes started to break beyond the melting temperature of pure PANI membrane indicating that the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The transport properties of UF membranes are significantly affected by the introduction of various additives, including polymeric additive, in the membrane composition [ 44 , 45 ]. In this work, partially cyclized polyacrylonitrile ( c PAN) was used as an additive to PAI.…”
Section: Resultsmentioning
confidence: 99%
“…The transport properties of UF membranes are significantly affected by the introduction of various additives, including polymeric additive, in the membrane composition [ 44 , 45 ]. In this work, partially cyclized polyacrylonitrile ( c PAN) was used as an additive to PAI.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, several studies demonstrated similar results where polyaniline was mixed with either PSF and poly­(vinylpyrrolidone) or PES and long chain acids. However, of all the polyaniline-blends reported, the contact angles generally remained within the range of 50° to 70° with minimal improvement in foulant rejection rates compared to pure PES or PSF membranes. , Notably, the surface hydrophilicity correlates positively with the loading of polyaniline; however, it is known that no solvents were able to incorporate more than 5 wt % of polyaniline due to the gelation effect. The gelation of polyaniline originates from the intermolecular hydrogen bonding between polyaniline chains, resulting in its low percentage of dispersion in solvents (Figure d,e).…”
Section: Polyblend Membranesmentioning
confidence: 99%
“…Often inorganic fillers are used for this purpose ; however, increasing attention is paid to polymer fillers. Such mixtures of polymers of different nature are widely used to produce materials for various purposes , including hybrid all‐polymeric membranes .…”
Section: Introductionmentioning
confidence: 99%